Focus on Basal Cell Carcinoma - Venura Samarasinghe; Vishal Madan; John T. Lear (Journal of Skin Cancer)
Nonmelanoma skin cancers (NMSCs), which include basal and squamous cell cancers are the most common human cancers. BCCs have a relatively low metastatic rate and slow growth and are frequently underreported. Whilst there is a definite role of sunexposure in the pathogenesis of BCC, several additional complex genotypic, phenotypic and environmental factors are contributory. The high prevalence and the frequent occurrence of multiple primary BCC in affected individuals make them an important public health problem. This has led to a substantial increase in search for newer noninvasive treatments for BCC. Surgical excision with predetermined margins remains the mainstay treatment for most BCC. Of the newer non-invasive treatments only photodynamic therapy and topical imiquimod have become established in the treatment of certain BCC subtypes, while the search for other more effective and tissue salvaging therapies continues. This paper focuses on the pathogenesis and management of BCC.